CAPACITY BUILDING OF MSMES THROUGH SIMPLE BOOKKEEPING EDUCATION IN KEBON MANGGIS VILLAGE, JAKARTA - Shanti Lysandra; Indupurnahayu Indupurnahayu (LPPM Univ. Ibn Khaldun Bogor, 2026)
This community service activity aims to increase the capacity of Micro, Small, and Medium Enterprises (MSMEs) in Kebon Manggis Village, Jakarta, in understanding and implementing structured simple business bookkeeping. The main problems faced by MSMEs in the region include the lack of understanding of basic accounting, the absence of separation between personal and business cash, and the absence of systematic transaction recording. Activities are carried out in the form of counseling, interactive discussions, and bookkeeping practices through case studies facilitated by lecturers and students. Evaluation through pre-test and post-test showed a significant improvement in understanding, with the average post-test score increasing from 3.54 to 4.5. These findings confirm that practice-based education methods are effective in improving participants' financial literacy and bookkeeping skills. Overall, this activity contributes to improving the financial governance of Kebon Manggis MSMEs and strengthens their ability to develop their businesses and access formal financing in a more professional manner.